Risk of acute myocardial infarction, stroke and thromboembolism following COVID-19 vaccination compared to testing positive for COVID-19 infection: a nationwide cohort study of 4.6 mio individuals. (3rd October 2022) - Lassen, M H; Modin, D; Skaarup, K G; Claggett, B; Solomon, S D; Fralick, M; Staehr-Jensen, J U; Sivapalan, P; Schou, M; Krause, T G; Hviid, A; Koeber, L; et al.
Abstract: Background: Large randomized controlled trials (RCT) have shown that COVID-19 vaccines are effective at preventing severe COVID-19. However, the RCT's are not powered to detect rare adverse events. It has been reported that the new mRNA based COVID-19 vaccines may increase the risk of thromboembolic and ischemic events. Likewise, thromboembolic and ischemic events are also known complications to infection with SARS-CoV-19. Currently, less is known about the risk-reward relationship of receiving an mRNA-based COVID-19 vaccine versus contracting COVID-19 infection with respect to thromboembolic and ischemic outcomes. Purpose: To compare the risk of thromboembolic and ischemic events following COVID-19 vaccination to the risk following infection with SARS-CoV-19. Methods: The study period was from March 2020 to August 2021. All individuals were >18 years old. The population was stratified into two different groups. The vaccinated group consisted of recipients of the first dose of either Moderna (mRNA-1273, n=488, 220) or Pfizer-BioNTech (BNT162b2 mRNA, n=3, 186, 164) vaccines. Individuals who had previously tested positive for SARS-CoV-19 were excluded. The other group consisted of individuals who had tested positive for SARS-CoV-19 in the same period who had not yet received their first vaccination dose (n=233, 926). The exposure period for both groups was set to 28 days following vaccination/testing positive for SARS-CoV-19 (Figure 1). Patient level data were obtained on all included individuals using nationwide registries. Primary outcomes were acute myocardial infarction (AMI), ischemic stroke, pulmonary embolism (PE), and deep venous thrombosis (DVT). Odds ratios were obtained from logistic regression models with the vaccinated group acting as reference. Multivariable models were adjusted for demographics and comorbidities. Results: In the vaccinated group, mean age was 53±19 years and 50.3% were female. In the group of participants testing positive for SARS-CoV-19, mean age was 42.1±17.4 years and 50.2% were female. In total, 773 suffered a stroke, 472 suffered a PE, 500 suffered an AMI, and 484 suffered a DVT during the 28-day exposure period. We observed an increased absolute risk of all outcomes for participants testing positive for SARS-CoV-19 as compared to participants being vaccinated (stroke: 0.049% vs 0.019%, p<0.001), (PE: 0.91% vs 0.0072%, p<0.001), (AMI: 0.021 vs 0.013, p=0.0004), and (DVT: 0.037% vs 0.011%, p<0.001). In multivariable models, participants testing positive for SARS-CoV-19 had a significantly increased risk of all outcomes compared to participants being vaccinated: (stroke: OR: 4.0, 95% CI: [2.9–5.6], p<0.001), (PE: OR: 38.6 95% CI: [30.3–48.5], p<0.001), (AMI: OR: 3.3, 95% CI: [2.1–5.00], p<0.001), and (DVT: OR: 5.3, 95% CI: [3.8–7.5], p<0.001) (Figure 2). Conclusion: The risks of thromboembolic and ischemic events were substantially higher after SARS-CoV-19 infection than after vaccination in the Danish population. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Gentofte University Hospital